Between Talents and Environment Impact during Pandemic COVID-19: Sketching the Career Perception in Vocational School - Abdul Hadi; Moh. Khoerul Anwar; Dhanang Suwidagdho; Ruly Ningsih (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
The purpose of this study was to determine and examine how student career perceptions are handled by students related to the environmental impact, talents, and COVID-19 circumstances on career services at State Vocational School 3 Klaten. This study uses a qualitative approach. Respondents were students and teachers of Guidance and Counselling at state vocational high school 3 Klaten. The findings indicate that students' career conceptions are connected to the environmental influence, skills, and the COVID-19 settings surrounding career services and that these beliefs favourably affect students' self-development. The findings indicate that the results of interviews with students regarding factors influencing their perceptions of career counselling and career development, including talents, promising career planning with parental support and the impact of the environment, career exploration, career development, and support from learning facilities during the COVID-19.